Analisis Kelayakan Finansial Driver Transportasi Online Di Kota Pekanbaru (Studi Kasus Grab) - Lapogi, M. Syafa’ad; Taufik, Hendra; Djuniati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Grab is a technology company from Malaysia that only provides public transportation transportation service applications, while the vehicle itself is owned by partners who have joined PT Grab Indonesia. The growth of online grab services in Pekanbaru which is so rapid and has succeeded in attracting many workers as drivers has become a phenomenon that needs attention. This study aims to analyze the financial feasibility of online transportation in the city of Pekanbaru, so that it can be used as a reference for people who want to join PT Grab Indonesia. This study uses 5 analytical methods, namely BEP to determine the principal return point, PBP to determine the length of time an investment or business returns, and IRR, NPV, BCR are used to determine the feasibility of a grab business. The results obtained from the feasibility test are IRR lower than the desired interest rate of 8,59%; 9,94% and 8,33%. NPV is negative, that is -118.156.430; -151.856.703 and -136.716.827. BCR value of 0,30; 0,33; 0,35, the BCR value obtained is less than 1. Based on financial analysis through the 3 methods, the business of grab drivers is declared unfeasible to run. Keywords: BEP, PBP, IRR, NPV and BCR.